PRESENT PERFECT VS SIMPLE PAST IN AMERICAN AND BRITISH ENGLISH: A DIACHRONIC STUDY - Rakhmatilloeva , Rukhshonabonu (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This paper examines the diachronic evolution of Present Perfect and Simple Past usage in American and British English from the 18th century to the present day. Through corpus-based analysis and historical linguistic research, this study reveals significant divergences between the two varieties, with American English showing a marked preference for Simple Past in contexts where British English maintains Present Perfect usage. The research demonstrates that this divergence intensified throughout the 20th century, reflecting broader patterns of linguistic change and standardization in both varieties.